2020
DOI: 10.31557/apjcc.2020.5.s1.171-173
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Cultural and Economic Impact of Corona Virus on Cancer Patients, Caregivers and Survivors

Abstract: Corona Virus Disease -19 (COVID-19) pandemic has a widespread impact on social, cultural and economic aspects of life. It has affected cancer patients in a big way because with onset of COVID-19 pandemic, the healthcare resources were diverted to handle Corona virus infection. The cancer patient, their caregivers and healthcare professional are in dilemma of whether to continue the treatment or stop it for some time till COVID-19 infection settled down. The long-lasting effect of COVID-19 pandemic on socio-eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Health care resources were mobilized to fight coronavirus infection. Cancer patients, their caregivers, and health care professionals do not know whether to continue treatment or wait for the COVID-19 pandemic to go away [ 43 ]. Büntzel et al [ 44 ] also showed that nearly half of the participants (43% of patients and 47% of physicians) expected negative consequences for patients’ physical condition, and that cancer patients felt emotional stress in 34% of their physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Health care resources were mobilized to fight coronavirus infection. Cancer patients, their caregivers, and health care professionals do not know whether to continue treatment or wait for the COVID-19 pandemic to go away [ 43 ]. Büntzel et al [ 44 ] also showed that nearly half of the participants (43% of patients and 47% of physicians) expected negative consequences for patients’ physical condition, and that cancer patients felt emotional stress in 34% of their physicians.…”
Section: Discussionmentioning
confidence: 99%
“…8 Similarly, cancer patients also experienced stress and anxiety due to this highly contagious disease. 9 Likewise, patients seeking dental treatment are also afraid to visit dentists. 10,11 It has always been challenging for the dental setup staff to maintain cross-infection control and, mainly, during dental procedures that produce aerosols.…”
Section: Introductionmentioning
confidence: 99%
“…14 Financial security in the form of insurance for the frontline health workers (who are at greater risk), should be introduced. 15 Countries must ensure that everyone can receive major services including health care, they must invest adequately in social protection programs to keep people safe and to shield them from the consequences of losing their livelihoods. 16…”
Section: Introductionmentioning
confidence: 99%